1965
DOI: 10.1042/bj0970485
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex and gonadal hormones on rat-liver and carcass lipids during the development of an essential fatty acid deficiency

Abstract: 1. Groups of intact male and female rats and castrated rats injected with oestradiol or testosterone were given a diet containing hydrogenated coconut oil for 9 weeks, and at intervals the amounts and fatty acid compositions of the carcass and liver lipids were determined. 2. Male rats grew faster and larger, and exhibited typical external essential fatty acid deficiency symptoms sooner than did females. Testosterone-treated castrated male rats were similar to males, and oestradiol-injected castrated male rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…These changes indicated that the biochemical features of EFA deficiency were rapidly reversed by either n-3 or n-6 fatty acids, although the effectiveness of n-3 and n-6 fatty acids was not exactly equal. Our results also showed a consistently higher level of 20:3n-9 and lower incorporation of n-3 and n-6 fatty acids in male than in female rats (Table I), confirming the reports that the female rat is less susceptible to EFA deficiency (1)(2)(3)(4)(5)(6)(7)(8). The differences between the sexes in EFA incorporation were considerably greater in the animals given fish oil.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…These changes indicated that the biochemical features of EFA deficiency were rapidly reversed by either n-3 or n-6 fatty acids, although the effectiveness of n-3 and n-6 fatty acids was not exactly equal. Our results also showed a consistently higher level of 20:3n-9 and lower incorporation of n-3 and n-6 fatty acids in male than in female rats (Table I), confirming the reports that the female rat is less susceptible to EFA deficiency (1)(2)(3)(4)(5)(6)(7)(8). The differences between the sexes in EFA incorporation were considerably greater in the animals given fish oil.…”
supporting
confidence: 94%
“…Male animals are generally more susceptible than female animals to essential fatty acid (EFA) deficiency (1)(2)(3)(4)(5)(6)(7)(8). Female rats retain higher levels of 20:4n-6 (arachidonic acid, AA) in tissues during EFA deficiency (3,7).…”
mentioning
confidence: 99%
“…Ever since, much research has been conducted on all aspects of EFAs including possible gender differences. Since the first study by Loeb and Burr [2], which reported a gender difference in EFA requirements, a series of studies in the 1960s by Lyman and Ostwald [3, 4] observed that female rats utilized EFAs more efficiently, especially arachidonic acid (ARA), an n-6 PUFA. This series of studies suggested that the gender difference in EFA metabolism was strongly related to sex and gonadal hormones, mainly estrogen and testosterone [36].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the present study clearly indicated that stearic acid and total saturated fatty acids are lower and linoleic acid, arachidonic acid, and total n-6 fatty acids are higher in elderly Japanese males than in females; these results were consistently shown in all the age groups with few exceptions and seem to be in disagreement with studies in experimental animals (10 , 11). Female rats are less sensitive to EFA deficiency than male rats and maintain higher concentrations of linoleic acid in adipose tissue (10). Reduction of post delta-6-desaturase products by dietary cholesterol administration is significantly greater in male rats than in females (11).…”
Section: Discussionmentioning
confidence: 87%